2008
DOI: 10.1007/s11999-008-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

How Are Outcomes Affected by Combining the Pemberton and Salter Osteotomies?

Abstract: The Pembersal operation combines features of the Pemberton and Salter osteotomies. Results have usually been reported in patients with dysplasia but without frank dislocation. We asked if the following factors influence the outcome of the Pembersal operation in patients with dislocated hips: triradiate cartilage damage causing early closure; the acetabular index improvement; and the age of the patient at time of operation. We assessed triradiate cartilage damage, a modified McKay clinical classification, aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
7
1
1
Order By: Relevance
“…In various studies, the redislocation rate after PA has been reported to be low (13,19). In the current study, although the difference was not statistically significant, redislocation was determined at a lower rate in the PA group.…”
Section: Discussioncontrasting
confidence: 64%
“…In various studies, the redislocation rate after PA has been reported to be low (13,19). In the current study, although the difference was not statistically significant, redislocation was determined at a lower rate in the PA group.…”
Section: Discussioncontrasting
confidence: 64%
“…The reported results of this operation are satisfactory; however, whether this procedure provides any advantages remains unclear [151,152] . In the older child or adolescent, if the triradiate cartilage remains open, the triple innominate osteotomy is the procedure of choice.…”
Section: Open Reduction and Hip Reconstructionmentioning
confidence: 99%
“…The key aim of pavlik harness focus on regain of normal improvement by atraumatic, repositioning and conservation of the hip joint functions. Primarily, skilful reduction of the hip depends on passive abduction and flexion [25]. In few cases which are having muscle imbalance like myelomening ocele, arthrogryposis (major stiffness), Ehlers-Danlos syndrome i.e.…”
Section: Non-surgical Treatment Of Ddhmentioning
confidence: 99%